2021
DOI: 10.1093/fampra/cmaa147
|View full text |Cite
|
Sign up to set email alerts
|

Health of war-affected Karen adults 5 years post-resettlement

Abstract: Background An estimated 140 000 refugees from Burma have resettled to the USA since 2009, comprising 21% of total resettlement in the USA over the last decade. Our objective was to describe patterns of longitudinal health outcomes in a cohort of Karen refugees resettled in the USA for 5 years, and to translate these findings to a primary healthcare context. Methods The study was a retrospective cohort study focused on the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…4 10 17 19 20 22 25 Results from asylum countries also showed that EHRs helped to develop focused screening guidelines and increase adherence to those guidelines. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] This in turn can lead to a reduction in health disparities between asylum seeking patients and the general population. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] This review identified a number of barriers to successful implementation of EHRs across development, deployment and data analysis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…4 10 17 19 20 22 25 Results from asylum countries also showed that EHRs helped to develop focused screening guidelines and increase adherence to those guidelines. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] This in turn can lead to a reduction in health disparities between asylum seeking patients and the general population. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] This review identified a number of barriers to successful implementation of EHRs across development, deployment and data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] This in turn can lead to a reduction in health disparities between asylum seeking patients and the general population. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] This review identified a number of barriers to successful implementation of EHRs across development, deployment and data analysis. 10 17 19 20 22 26 27 31 45 48 49 This review also found improved usability in EHR systems that were easily adaptable or able to interlink with systems management.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations